Evaluation of biodegradability and biotoxicity of surfactants in soil. Issue 49 (15th June 2017) - Li, Guixiang; Lan, Guihong; Liu, Yongqiang; Chen, Chen; Lei, Lin; Du, Jiao; Lu, Yingchun; Li, Qiang; Du, Guoyong; Zhang, Jihong
Abstract : In this study, the biodegradability and biotoxicity of four surfactants, i.e. modified heterogeneous alcohol ether, fatty acid methyl ester ethoxylates, Tween-80 and rhamnolipid, under natural soil conditions were investigated. Abstract : In this study, the biodegradability and biotoxicity of four surfactants, i.e. modified heterogeneous alcohol ether with an 8–12 carbon alkylic chain, fatty acid methyl ester ethoxylates, Tween-80 and rhamnolipid (a kind of biosurfactant), under natural soil conditions were investigated. Batch experiments of degradation with an initial concentration of surfactants of 120 mg kg −1 in soil were carried out at room temperature varying from 15 °C to 22 °C. The concentrations of surfactants over time were measured and metabolites of the surfactants were characterized by gas chromatography-mass spectrometry. In addition, the amount of microorganisms in soil over time was measured by using agar plates. The results showed that fatty acid methyl ester ethoxylates had the highest biodegradation rate followed by rhamnolipid, Tween-80 and modified heterogeneous alcohol ether. A biotoxicity assay based on a photobacterium revealed that these surfactants had low toxicity. It is concluded that the fatty acid methyl ester ethoxylates are the most environmentally friendly surfactants among the four surfactants studied.